The influence of treatment on the development of leishmaniasis recidiva cutis: a 17‐year case–control study in Midwestern Brazil. (21st March 2014) - Gomes, C.M.; Cesetti, M.V.; de Morais, O.O.; Mendes, M.S.T.; Roselino, A.M.; Sampaio, R.N.R.
Abstract Background The recurrence of American cutaneous leishmaniasis (ACL) in patients experiencing a long‐term cure is often called leishmaniasis recidiva cutis (LRC). LRC is considered an unusual form of ACL. Objective This study aims to estimate the incidence of LRC in ACL patients evaluated at a tertiary dermatologic centre in Midwestern Brazil. We also aim to evaluate the association between various treatment regimens and the development of LRC using multivariate analysis in a case–control study. Methods We performed a 17‐year epidemiological study using data from patients treated at our dermatologic centre from July 1994 to December 2011. A retrospective analysis was then performed to estimate risk and protective factors related to clinical presentation. We also assessed the influence of treatment regimens in the development of LRC. Results The incidence of LRC among ACL patients was 1.34%. The analysis included 105 patients; 82 patients (78%) were in the control group, and 23 patients (22%) were in the LRC case group. The data analysis indicated that the standard treatment N‐methylglucamine antimoniate (N‐MA) reduced the development of LRC in bivariate (odds ratio (OR) = 0.34; 95% CI = 0.13–0.91) and multivariate analyses (OR = 0.16; 95% CI = 0.03–0.86; P = 0.03). However, no differences in LRC incidence were observed when the standard treatment N‐MA and alternative drugs, such as pentamidine and amphotericin B, were considered (OR = 0.47; 95% CI = 0.16–1.35) Conclusion We conclude that the standard treatment N‐MA, as proposed by the Brazilian Ministry of Health, is effective in the prevention of LRC. Although other drugs have shown promising results in LRC, more scientific evidence is needed to assess their efficacy compared with N‐MA.